Dialogue and its functions in pre-Islamic poetry - Attia, Zainab Kazem; Nia, Dr. Maryam Hekmat; Firouzjai, Hussein Tatbard. (Thi Qar Arts Journal, 2024)
Dialogue in literature is a written or spoken exchange between two or more characters. It is a form of communication that allows characters to express their needs, desires, inclinations, attitudes, and problems. Dialogue has been known since ancient times as a necessity for human interaction. It was used in pre-Islamic poetry, giving poetic texts artistic value. In this article, we aim to shed light on dialogue in pre-Islamic poetry through an analytical critical approach. Dialogue in Pre-Islamic Poetry: Dialogue was prevalent in pre-Islamic poetry, often used to express sorrow, grief, and emotions by various poets. Notable examples include: • Imru’ al-Qais in his dialogues with his beloveds, Salma and Layla. • Zuhayr ibn Abi Sulma in his dialogue with Umm Awfa. • Amr ibn Kulthum, Tarafa ibn al-Abd, and Al-Harith ibn Hilliza al-Yashkuri in their dialogues with their tribes. Different types of dialogue appeared, such as: • Monologic Dialogue: A conversation with oneself. • Self-Dialogue: Reflecting internal thoughts. • Supplicatory Dialogue: Addressing a higher power or oneself. • Dialogue with Others: Interacting with other characters. The purposes of these dialogues varied, including expressing love for the beloved, longing for the homeland, or raising awareness among people. The dialogues were characterized by pride in the poetry of Amr ibn Kulthum, sorrow in the poetry of Tarafa ibn al-Abd, and wisdom in the poetry of Al-Harith ibn Hilliza.